Distribution of microRNA biomarker candidates in solid tissues and body fluids - Fehlmann, Tobias (RNA Biol, 2016)
Small non-coding RNAs, especially microRNAs, are discussed as promising biomarkers for a substantial number of human pathologies. A broad understanding in which solid tissues, cell types or body fluids a microRNA is expressed helps also to understand and to improve the suitability of miRNAs as non- or minimally-invasive disease markers. We recently reported the Human miRNA Tissue Atlas (http://www.ccb.uni-saarland.de/tissueatlas) containing 105 miRNA profiles of 31 organs from 2 corpses. We subsequently added miRNA profiles measured by others and us using the same array technology as for the first version of the Human miRNA Tissue Atlas. The latter profiles stem from 163 solid organs including lung, prostate and gastric tissue, from 253 whole blood samples and 66 fractioned blood cell isolates, from body fluids including 72 serum samples, 278 plasma samples, 29 urine samples, and 16 saliva samples and from different collection and storage conditions. While most miRNAs are ubiquitous abundant in solid tissues and whole blood, we also identified miRNAs that are rather specific for tissues. Our web-based repository now hosting 982 full miRNomes all of which are measured by the same microarray technology. The knowledge of these variant abundances of miRNAs in solid tissues, in whole blood and in other body fluids is essential to judge the value of miRNAs as biomarker.